Pengaruh Profitabilitas, Risiko Keuangan, dan Pertumbuhan Perusahaan terhadap Manajemen Laba pada Sektor Perbankan di Bursa Efek Indonesia - Musdalifa; Vitayanti fattah; Munawarah; Suryadi Samudra (JURNAL MANAJEMEN MOTIVASI, 2026)
The stability of earnings reporting in the banking sector is influenced by profitability, financial risk, and firm growth, which may encourage earnings management practices. This study aims to analyze the effect of profitability, financial risk, and firm growth on earnings management in the banking sector listed on the Indonesia Stock Exchange during the 2021–2024 period. The research applies a quantitative approach using secondary data. Samples were selected through purposive sampling, resulting in 27 banks with 108 observations. The analysis was conducted using panel data regression. The results show that profitability (ROA), financial risk (NPL), and firm growth have a positive and significant effect on earnings management, both partially and simultaneously. The coefficient of determination is 64.12%. These findings are important for investors and regulators in assessing the quality of banking earnings.